The Development Of Gas Turbine Engine Using Turbocharger - Isa, Mohd Norhafidan (Universiti Sains Malaysia, 2018)
Gas turbine engine using turbocharger (also known as micro gas turbine engine) is a small-scale gas turbine engine that can be used to drive a portable power generator and has a potential to produce low emission. In this project, a small gas turbine engine is developed using a turbocharger from a car engine. This thesis is focused in designing and fabricating required components and supporting/auxiliary systems for the operational of the gas turbine engine which are ignition system, fuel injection system, lubrication system, air ducting and combustion chamber. In this report, the designing and fabricating method for all auxiliary systems and combustion chamber are presented. The ignition system used conventional spark plug system to ignite the fuel-air mixture in the combustion chamber. The fuel used is butane gas which is a type of fuel that used in cooking purpose. Lubrication system is required since the rotating shaft inside the turbocharger which is directly connected with compressor wheel and turbine wheel will rotate at several thousand revolutions per minute during the operation. A simple lubrication system is designed and fabricated to deliver an amount of lubricating oil on the rotating shaft to reduce wear and for longer lifespan. The combustion chamber is the most crucial part. It consists of two main parts which are flame housing and flame tube. These parts are carefully designed to get the perfect combustion for the engine to self-sustaining the combustion process. In this report, the method in designing the combustion chamber also presented. The designed combustion chamber is studied to determine whether it is suitable for this project or not. After all systems and combustion chamber are completely fabricated, the system is assembled with the turbocharger and the engine is tested for several times. The operational performance of all system and the gas turbine engine also are observed during the engine operation. All problems encountered in each system and its solutions are presented.